Study on reasonable determination method of XRD spectral parameters and its response to coal graphitization - Guangqing HU; Feng HAN; Wei LIU; Yuhang GAO; Dun WU; Wenyong ZHANG; Huihui LUO; Yanhai ZHANG; Biao FU (Meitan kexue jishu)
Under the background of comprehensive utilization and carbon neutralization of coal-series associated minerals, coal-series graphite has attracted more and more attention from scholars at home and abroad. As one of the important characterization means to study the degree of molecular order and determine the structure of coal microcrystals, XRD spectrum analysis is of great significance to reveal the relationship between the order of carbon microcrystal arrangement and the graphitization degree of coal. In order to obtain the XRD related index parameters of coal more scientifically, quickly and effectively, and constantly improve the evaluation index system of coal-series graphite, taking 7 pairs of metamorphic coals in Huaibei coalfield as the research object, with the help of coal quality analysis, vitrinite reflectance and XRD, the effects of different peak fitting methods and different sample pretreatment methods on XRD spectral parameters were studied, and the effective determination method and response law of coal-series graphite evaluation index based on XRD spectral analysis were discussed. Research shows that; ① Different peak fitting methods have great influence on the evaluation results of coal-series graphite, and whether the bottom back is deducted has more obvious influence on the experimental results than whether the baseline is removed; ② Whether the (γ) peak is considered has a great influence on the experimental results, which directly affects the classification and identification results of the graphitization degree of the samples; ③ By analyzing the XRD spectrum curves of different raw coal and standard Si powder ratios, it is concluded that under the mass ratio of raw coal/SiO2 ≈3∶1, the 2θ value of (002) peak of raw coal sample can be effectively determined by internal standard method, and the experimental effect is equivalent to that of demineralization method. ④ Vdaf and H/C can be recommended as the main coal quality parameters, while La, La/Lc and d002 can be recommended as the main structural parameters. Among them, Vdaf < 20%, H/C > 0.035, La < 4 nm, La/Lc < 1 and d002<0.344 nm can be used as the critical marks for the coal metamorphism in Huaibei coalfield to enter the semi-graphitization stage. The above research results provide a reference for the optimization of evaluation index and the construction of identification system of coal-series graphite in Huaibei coalfield.